Eating Disorders in Male Athletes. (July 2020) - Eichstadt, Madison; Luzier, Jessica; Cho, Daniel; Weisenmuller, Chantel
Context: Eating disorders (EDs) in male athletes are potentially debilitating disorders with significant medical, psychological, and athletic performance consequences. Evidence Acquisition: Searches were performed across PubMed, EBSCOhost, and PSYCinfo from 1990 to 2019. Keywords searched were eating disorder, male, athlete, anorexia nervosa, bulimia nervosa, muscularity, muscle dysmorphia, and sports . Search results included articles written in the English language and encompassed reviews, empirical studies, and theoretical articles. Study Design: Clinical review. Level of Evidence: Level 3. Results: EDs among male athletes may lead to serious negative outcomes, including increased susceptibility to injury, inconsistent performance, problematic recovery, muscle deficiencies, impairment of optimal athletic functioning, and medical, social, and emotional problems. Male athletes with EDs may be more difficult to identify and diagnose for a variety of reasons related to differential presentation of symptoms, secretiveness or shame around behaviors, and sex-related stigma. Conclusion: Professionals working closely with athletes are uniquely positioned to identify and screen those who may require further evaluation and treatment.